Effect of sumatriptan following simulated traumatic brain injury in rats - GÜVENÇ, YAHYA (My University, 2022)
Introduction: Traumatic brain injury (TBI) continues to be a devastating problem in developing countries. The inevitable traumatic effect is followed by a secondary phase of neuroinflammation leading to increased morbidity and mortality. Numerous agents and treatment modalities have been tested to date. The first clinically available triptan used to treat migraine, sumatriptan (SUM), has been evaluated for cerebral, testicular and renal ischemia previously but to our knowledge this is the fi rst paper where its anti-inflammatory and anti-oxidative effects after experimental TBI in rats has been evaluated. Aim: Employing an experimental trauma technique, we aimed to investigate whether SUM has ameliorating effects on the infl ammatory phase of TBI via neurological, histological and biochemical analyses. Methodology: Twenty-three Wistar albino rats were randomly divided into three groups: control, trauma and trauma + SUM. The two latter groups underwent experimental diffuse cortical injury mimicking TBI. The subjects underwent neurological assessment via the Garcia Test, histological analysis via a novel scoring system and biochemical analyses of neuron specifi c enolase (NSE), S-100B, caspase-3 (CASP3), and rat thiobarbituric acid reactive substances (TBARS) levels. Results: SUM receiving group had a better Garcia Test score (P < 0.001), higher anti-inflammatory score (P = 0.004) and higher neuroprotective score (P < 0.001) along with a better histopathological score when compared with the trauma group. SUM receiving group had lower levels of S100B, CASP3 and TBARS. SUM was unable to reduce NSE levels. Conclusion: SUM may prove to be beneficial in decreasing mortality and morbidity rates after TBI through its anti-inflammatory and anti-oxidative effects. The novel scoring system used in this study may be a valuable tool for similar experiments.

Úvod: Traumatické poranění mozku (traumatic brain injury; TBI) je v rozvojových zemích stále velmi vážným problémem. Nevyhnutelným výsledkem traumatu je sekundární fáze s neuroinfl amací, která vede ke zvýšené morbiditě a mortalitě. Do současné doby byly tetovány různé účinné látky a léčebné modality. První klinicky dostupný tryptan, který byl použit k léčbě migrény – sumatriptan (SUM) – byl předtím hodnocen při cerebrální, testikulární a renální ischemii, ale pokud je nám známo, toto je první článek, který hodnotí jeho protizánětlivé a antioxidační vlastnosti po experimentálním TBI u potkanů. Cíl: Při použití naší techniky experimentálního traumatu jsme si dali za cíl zjistit, zda SUM zlepšuje stav při zánětlivé fázi TBI, a to prostřednictvím neurologické, histologické a biochemické analýzy. Metodologie: Dvacet tři potkanů kmene Wistar albino bylo náhodně rozděleno do tří skupin: kontrolní skupina, skupina s traumatem a skupina s traumatem, které byl podáván SUM. U posledních dvou skupin bylo vyvoláno experimentální difuzní poranění kortexu, které simulovalo TBI. Subjekty podstoupily neurologické hodnocení prostřednictvím Garciova testu, histologické vyšetření pomocí nového skórovacího systému a biochemickou analýzu hladin neuron specifi cké enolázy (NSE), S100B, kaspázy-3 (CASP3) a tzv. „rat thiobarbituric acid reactive substances“ (TBARS). Výsledky: Skupina, které byl podáván SUM, měla lepší skóre Garciova testu (p < 0,001), zvýšený protizánětlivý účinek (p = 0,004) a neuroprotektivní účinek (p < 0,001) a zároveň sníženou hladinu TBARS (p < 0,05), ale v porovnání se skupinou s traumatem měly podobné hladiny S100B, CASP3 a NSE. Závěr: Podání SUM může přinést prospěch z hlediska snížení mortality a morbidity po TBI vlivem jeho protizánětlivého a antioxidačního účinku. Nový skórovací systém použitý v této studii může být u podobných experimentů užitečným nástrojem.
Účinek sumatriptanu po simulovaném traumatickém poranění mozku u potkanů
Keywords: SİNİR BİLİMİ; Sinirbilim ve Davranış; Yaşam Bilimleri (LIFE); CERRAHİ; Klinik Tıp; Klinik Tıp (MED); NEUROSCIENCES; NEUROSCIENCE & BEHAVIOR; Life Sciences (LIFE); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); sumatriptan; trauma; brain injury; neuroprotective; anti-inflammatory; anti-oxidative; NEURON-SPECIFIC ENOLASE; NITRIC-OXIDE; MODEL; PROTEIN; Sumatriptan; trauma; brain injury; neuroprotective; anti-infl ammatory; anti-oxidative; sumatriptan; trauma; poranění mozku; neuroprotektivní; protizánětlivý; antioxidační